Noise Level Mapping in Kopelma Darussalam Banda Aceh City - Adian Aristia Anas; Anggi Santia; Nurul Kamal; Nurhadia Humaira (Al-Ard: Jurnal Teknik Lingkungan, 2022)
Kopelma Darussalam is an education center in The Aceh Province which has the area of ​​206.2 hectares. There are 6 schools and 2 nerby public universities (Ar-Raniry State Islamic University and Syiah Kuala University) in the region. Transportation activities in Kopelma Darussalam remarkably can increase noise level primarily during studying and working hours. The purpose of this research is to determine the noise level and to map the noise distribution in Kopelma Darussalam. The mapping is created by using Surfer 13 software. This methode of this study is quantitative descriptive research. Primary data is obtained by using a Sound Level Meter (SLM) to measure noise levels on weekdays and holidays both outsides and indoors at 8 sampling locations. The data is then analyzed by using statistical equations provided by Decree of the State Minister of the Environment KEP-48/MENLH/11/1996. The results shows that the noise level at Kopelma Darussalam is in a noisy condition as it ultimately has exceeded the quality standard of 55 dBA, especially on weekdays at 2.00 to 5.00 p.m. The map of noise distribution at Kopelma Darussalam shows that the highest noise is coloured in red (≥ 67 dBA). This value has exceeded the quality standard which leads lecturers and students necessarily to speak louder in classrooms. Keywords: Noise, transportation, motor vehicle, mapping, Surfer 13.